Treating high density lipoprotein cholesterol (HDL-C): Quantity versus quality - Pirillo, A.; Norata, Giuseppe; Catapano, A. (2013)
Low density lipoproteins (LDL) and high density lipoproteins (HDL) are independent risk factors for coronary heart disease (CHD); decreasing LDL-cholesterol (LDL-C) levels with statin therapy represents the primary goal in the management of cardiovascular disease. However, despite the efficacy of statins in reducing cardiovascular morbidity and mortality, a significant residual risk has been observed even after reaching the LDL-C target, suggesting that other risk factors beyond LDL-C should be addressed, including low levels of HDL-cholesterol (HDL-C). Several clinical trials have shown an inverse relationship between HDL-C levels and cardiovascular risk, and 1 mg/dl increment in HDL-C is associated in epidemiological studies with a 2-3% decrease in cardiovascular risk, suggesting that raising HDL-C levels might have beneficial effects to reduce cardiovascular disease. However, several lines of evidence indicate that the functional properties of HDL may be relevant as well. In patient with CAD and normal HDL-C levels, HDL exhibit significantly reduced protective functions, and rather appear to be pro-atherogenic; on the other hand some genetic mutations causing low levels of HDL-C are not associated with increased atherosclerosis. Furthermore, although niacin significantly increased HDL-C levels, no further clinical benefit was observed from the addition of niacin to statin therapy, suggesting that increasing HDL-C levels is not sufficient and perhaps functional properties of HDL must be considered when choosing a therapeutic strategy to reduce the residual cardiovascular risk. © 2013 Bentham Science Publishers.